MOTIVATION OF FOSTER CHILDREN IN PARTICIPATING IN LEARNING AT LPKA KUTOARJO - Suryaningtyas, Nugraheni; Tando, Cahyoko Edi; Equatora, Muhammad Ali (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the motivation of foster children in participating in learning at LPKA Kutoarjo. The success of schooling is significantly impacted by students' motivation to study, particularly those who are receiving coaching. Data for this study was gathered through interviews using descriptive qualitative approaches. Foster children, LPKA officers, and PKBM "Tunas Mekar" tutors made up the research informants. The findings demonstrated that foster children's motivation is impacted by both external and internal elements, including the learning environment and tutor assistance, as well as internal factors like the desire to grow as individuals and create a better future. However, barriers like inadequate educational resources and a lack of family support have an impact on kids' motivation to learn. This study sheds light on the crucial role that educational coaching plays in LPKA and recommends enhancing Keywords: Learning Motivation; Fostered children; Education Coaching